2020
DOI: 10.3390/insects11080497
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities in Three Parts of Intestinal Tracts of Carpenter Bees (Xylocopa tenuiscapa)

Abstract: This study investigated different bacterial communities in three intestinal parts (foregut, midgut and hindgut) of Xylocopatenuiscapa to understand the roles of gut bacteria. Our phylogenetic analysis revealed that X. tenuiscapa is closely related to Xylocopa latipes. The 16S rRNA gene in the genomic DNA samples from the gut was examined by illumina (Solexa) and a total of 998 operational taxonomic unit (OTUs) clusters were found. Taxonomic classification identified 16 bacterial phyla and unclassified bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
4
6
0
Order By: Relevance
“…The bacterial taxa that we describe here are comprised of primarily bee-associated taxa or those that associate with diverse insects, similar to the previously characterized Xylocopa tenuiscapa (Subta et al 2020). Xylocopa gut samples containedBombilactobacillus (previously Lactobacillus Firm4),Bombiscardovia ( Bifidobacteriaceae), and Lactobacillus bxid5692 (similar to Lactobacillus Firm5) in nearly every individual, often with multiple co-occurring ASVs, and typically at high abundance, similar to previously characterized Apis andBombus species (Kwong et al 2017).…”
Section: Discussionsupporting
confidence: 72%
“…The bacterial taxa that we describe here are comprised of primarily bee-associated taxa or those that associate with diverse insects, similar to the previously characterized Xylocopa tenuiscapa (Subta et al 2020). Xylocopa gut samples containedBombilactobacillus (previously Lactobacillus Firm4),Bombiscardovia ( Bifidobacteriaceae), and Lactobacillus bxid5692 (similar to Lactobacillus Firm5) in nearly every individual, often with multiple co-occurring ASVs, and typically at high abundance, similar to previously characterized Apis andBombus species (Kwong et al 2017).…”
Section: Discussionsupporting
confidence: 72%
“…Many bacterial taxa in the gut of most Xylocopa are considered core bacterial symbionts of corbiculate bees (Figures 4–6; Subta et al, 2020, Holley et al, 2022). Bombilactobacillus (previously Lactobacillus Firm4), Bombiscardovia (Bifidobacteriaceae) and Lactobacillus bxid5692 (related to Lactobacillus Firm5) were detected in nearly every individual, similar to previously characterized Apis and Bombus species (Killer et al, 2010; Kwong et al, 2017; Parmentier et al, 2018), suggesting these genera have a larger host range than previously recognized (Alberoni et al, 2019; Hammer et al, 2021; Kwong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the microbiome of carpenter bees—close relatives of corbiculates with contrasting social structure—may offer insights into the role of sociality in the evolution of the bee microbiome. Recent sequencing efforts in Xylocopa tenuiscapa document gut communities dominated by Lactobacillales, Enterobacteriaceae and Bifidobacteriacae (Subta et al, 2020), while three of the four Xylocopa species from the central and eastern USA hosted Bifidobacterium , Bombiscardovia , Bombilactobacillus , Apilactobacillus and Lactobacillus , in striking similarity to social corbiculate microbiomes (Holley et al, 2022). These results suggest that the bacterial communities of some Xylocopa may resemble those of social corbiculates, but it is unclear if other Xylocopa species with well‐studied social structure exhibit similar microbiome composition.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, less is known for other pollinators and especially for solitary bees probably because of the difficulties in collection and study. The few studies available on non-social bee species showed a more variable and less distinctive microbiome if compared to social bees [ 66 68 ]. Solitary bees are also usually prone to maternally transmitted bacteria [ 69 ] and the acquisition of a homogeneous gut microbiome is presumably harder, therefore complicating the determination of the core taxa inhabiting the gut.…”
Section: Discussionmentioning
confidence: 99%